CLASS STRUGGLE IN THE LITERARY REALM: INSIGHTS FROM TERRY EAGLETON'SMARXISM AND LITERARY CRITICISM (CAHIERS MAGELLANES-NS, 2024)
Terry Eagleton's Marxism and Literary Criticism provides a foundational exploration of howMarxist theory applies to the study of literature. His analysis offers insights into the class struggleinherent in literary production, distribution, and reception. Terry Eagleton builds on the Marxist conceptof the base (economic foundation) and superstructure (cultural and ideological institutions). Literature,as part of the superstructure, both reflects and reinforces the economic base. Literary works can revealthe class conflicts and economic conditions of their time. This paper focuses on the class struggle in theliterary realm with reference to Terry Eagleton's Marxism and Literary Criticism.